A short note on the Guyana-Suriname arbitration - Scotland, Barton (2008)
Looks at the position of the parties and the findings of the Tribunal. Concludes that the decision of the Tribunal settles the maritime boundary demarcation between Guyana and Suriname but there is still much to be discussed between Guyana and Suriname.